Adsorption equilibrium of carbon dioxide on ammonia-modified activated carbon - Shafeeyan, M.S.; Daud, Wan Mohd Ashri Wan; Shamiri, A.; Aghamohammadi, N. (Elsevier, 2015)
The equilibrium adsorption isotherms of carbon dioxide on a commercial granular activated carbon (GAC) and an ammonia-modified GAC (OXA-GAC) were measured using a static volumetric method. CO2 adsorption measurements were performed at three different temperatures (303, 318, and 333 K), and pressures up to 1 atm. The obtained equilibrium data were fitted to the Freundlich, Sips, and Toth isotherms using a semi-empirical approach to differentiate the contributions of physical and chemical adsorption to the total CO2 uptake. The isotherm parameters were determined independently for each mechanism by non-linear regression. To evaluate the adequacy of the fit of the isotherm models, two different error functions (i.e., the average relative error and the nonlinear regression coefficient) were calculated. The Toth semi-empirical equilibrium model provided the best fit to the experimental data, with average relative errors of less than 3% observed at all temperatures. The isosteric heats of CO2 adsorption onto the ammonia-modified adsorbent and onto the untreated adsorbent were determined using the Clausius-Clapeyron equation. The loading dependence of the isosteric enthalpy of CO2 adsorption over the OXA-GAC reflected an energetic heterogeneity of the adsorbent surface. The initial isosteric heats of adsorption of 70.5 kJ mol(-1) and 25.5 kJ mol(-1) correspond to the adsorption of CO2 on the modified and untreated adsorbents, respectively, and these values were in excellent agreement with the zero-coverage heats of adsorption obtained using the temperature-dependent parameters of the proposed model. (C) 2015 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.